A history of online information services, 1963-1976 - Bourne, Charles P. (MIT Press, 2003)
Every field of history has a basic need for a detailed chronology of what happened: who did what when. In the absence of such a resource, fanciful accounts flourish. This book provides a rich narrative of the early development of online information retrieval systems and services, from 1963 to 1976--a period important to anyone who uses a search engine, online catalog, or large database. Drawing on personal experience, extensive research, and interviews with many of the key participants, the book describes the individuals, projects, and institutions of the period. It also corrects many common errors and misconceptions and provides milestones for many of the significant developments in online systems and technology.